Freedom of information and the developing world : the citizen, the state and models of openness - Darch, Colin (Chandos information professional series., 2010)
Rather than simply summarising the state of play in African countries and elsewhere, this book identifies and makes explicit the assumptions about the citizen's relationship to the state that lie beneath Freedom of Information (FoI) discourse. The book goes on to test them against the reality of the pervasive politics of patronage that characterise much of African practice.